MECP2 coding sequence and 3'UTR variation in 172 unrelated autistic patients - Coutinho, Ana M. (2007)
Mutations in the coding sequence of the methyl-CpG-binding protein 2 gene (MECP2), which cause Rett syndrome (RTT), have been found in male and female autistic subjects without, however, a causal relation having unequivocally been established. In this study, the MECP2 gene was scanned in a Portuguese autistic population, hypothesizing that the phenotypic spectrum of mutations extends beyond the traditional diagnosis of RTT and X-linked mental retardation, leading to a non-lethal phenotype in male autistic patients. The coding region, exon-intron boundaries, and the whole 3'UTR were scanned in 172 patients and 143 controls, by Detection of Virtually All Mutations-SSCP (DOVAM-S). Exon 1 was sequenced in 103 patients. We report 15 novel variants, not found in controls: one missense, two intronic, and 12 in the 3'UTR (seven in conserved nucleotides). The novel missense change, c.617G > C (p.G206A), was present in one autistic male with severe mental retardation and absence of language, and segregates in his maternal family. This change is located in a highly conserved residue within a region involved in an alternative transcriptional repression pathway, and likely alters the secondary structure of the MeCP2 protein. It is therefore plausible that it leads to a functional modification of MeCP2. MECP2 mRNA levels measured in four patients with 3'UTR conserved changes were below the control range, suggesting an alteration in the stability of the transcripts. Our results suggest that MECP2 can play a role in autism etiology, although very rarely, supporting the notion that MECP2 mutations underlie several neurodevelopmental disorders.